In obesity even young women suffer from urogynecological symptoms - Brucker, Janina; Wagner, Ina; Rudofsky, Gottfried; Rauch, Geraldine; Sohn, Christof; Brocker, Kerstin A. (Archives of gynecology and obstetrics, 2017)
Purpose: To evaluate the occurrence of urogynecological symptoms in obese women treated in a university outpatient clinic for obesity, setting a focus on younger women.MethodsIn this explorative, prospective, cross-sectional, single-center, multidisciplinary clinical trial, all consecutively recruited women received the Prolapse Quality of Life questionnaire (P-QOL) for data acquisition. The total study population (TSP) and a subgroup (SG) aged 18-49 years were evaluated descriptively regarding symptom demonstration.Results: Of the TSP (n = 166, mean age 40.2, standard deviation (SD) 12.98, mean body mass index (BMI) 45 kg/m2, SD 8.44) 105 (63%) and of the SG (n = 125, mean age 34.6, SD 9.29, mean BMI 44.9 kg/m2, SD 8.26) 72 (58%) women suffered from urinary incontinence (UI) being most impaired by stress urinary incontinence (SUI; TSP: 25%; SG: 27%) and least by urge urinary incontinence (UUI; TSP: 15%; SG: 11%). A significant correlation in the TSP between UI and age was detectable (p < 0.001, r φ = 0.37), but not between UI and BMI (p = 0.296, r φ = 0.08). The highest QOL impairment is detected for the domain general health perceptions [GHP; TSP & SG score >50 (score scale 0-100)]. Women with UI are significantly more affected than women with pelvic organ prolapse (GHP UI: TSP p = 0.04, SG p = 0.037; GHP POP: TSP p = 0.081, SG p = 0.659).ConclusionsA remarkable number of young obese women mentioned urogynecological symptoms and quality-of-life impairment. The P-QOL questionnaire proved to be an easily applicable tool to scan for concerned obese women. Its use in non-urogynecological departments, as performed, enables an early introduction of symptomatic women to urogynecologists, possibly preventing future growing urogynecological health issues.